2019
DOI: 10.1111/jdv.15680
|View full text |Cite
|
Sign up to set email alerts
|

Associations of pigmentary and naevus phenotype with melanoma risk in two populations with comparable ancestry but contrasting levels of ambient sun exposure

Abstract: Background: People at high risk of developing melanoma are usually identified by pigmentary and naevus phenotypes. Objective: We examined whether associations of these phenotypes with melanoma risk differed by ambient sun exposure or participant characteristics in two population-based, case-control studies with comparable ancestry but different ambient sun exposure. Methods: Data were analysed from 616 cases and 496 controls from the Australian Melanoma Family Study and 2,012 cases and 504 controls from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
(60 reference statements)
2
17
1
Order By: Relevance
“…Most epidemiological studies that have examined this hypothesis have focused on the association of sun exposure (or a proxy such as solar elastosis) with melanoma risk stratified by anatomical site 14,16,17 . Few studies have examined associations of other risk factors by anatomical site, such as pigmentary and naevus characteristics, despite their strong associations with melanoma risk and the importance of host characteristics in the dual pathway hypothesis 3,6,12,18–22 . Most of these studies have been case‐only designs with small sample sizes and limited statistical power, have captured data for only a few risk factors or have been limited to one sex 3,14,23 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most epidemiological studies that have examined this hypothesis have focused on the association of sun exposure (or a proxy such as solar elastosis) with melanoma risk stratified by anatomical site 14,16,17 . Few studies have examined associations of other risk factors by anatomical site, such as pigmentary and naevus characteristics, despite their strong associations with melanoma risk and the importance of host characteristics in the dual pathway hypothesis 3,6,12,18–22 . Most of these studies have been case‐only designs with small sample sizes and limited statistical power, have captured data for only a few risk factors or have been limited to one sex 3,14,23 .…”
mentioning
confidence: 99%
“…Cutaneous melanoma incidence is increasing in many countries with populations of predominantly European origin, despite improvements in prevention 1,2 . Most of the risk for melanoma is driven by intensity and pattern of sun exposure, host factors such as pigmentary phenotypes, propensity to develop naevi, genetic susceptibility and the complex association among these factors 3–6 . The aetiology of melanoma is also indicated by the anatomical site on which it develops, 7,8 with two main biological pathways proposed 9–12 .…”
mentioning
confidence: 99%
“…Our study was limited by the relatively small sample size, such that we lacked power to detect significant associations. However, the differences in accuracy of self‐reported naevus density observed by age, and previous keratinocyte cancer, in addition to the previously reported sex and melanoma history, approached significance and warrant further investigation. If these differences prove significant in larger studies, the effect on risk modelling and prediction requires exploration and correction sought, for example, using Bayesian methodology.…”
mentioning
confidence: 99%
“…Melanocytic naevi are one of the strongest risk factors for melanoma, 1,2 and the number of naevi on a person’s body is commonly used as a marker for level of risk 3 . For example, a meta‐analysis suggested that people with ≥ 25 common naevi and/or at least one atypical naevus form a high‐risk group, 1 and international clinical practice guidelines commonly consider people with > 100 common naevi or more than five atypical naevi to be a group at very high risk 3 .…”
mentioning
confidence: 99%
“…3 It is well known that naevi predominantly originate in childhood, and their development is influenced by sun exposure and genetic factors. 2,4,5 However, cross-sectional studies have indicated that naevus counts decrease during adulthood, particularly after age 40 years, which would make naevi a less reliable indicator of risk at older ages.…”
mentioning
confidence: 99%